Kontrol Yuridis PTUN dalam Menyelesaikan Sengketa Tata UsahaNegara di Tingkat Daerah - Budi Agus Riswandi (Jurnal Hukum IUS QUIA IUSTUM, 2007)
The dispute settlement of administrative law procedures which has local nature will be resolved under two steps. The first step through the District Administrative Law judicature and the second step it will be  held by the High Administrtive Law Judicature. The dispute settlement of administrative law procedure is an  ultimum remidium. It means if the dispute can be settled by using negotiation among  parties ( individual, corporate bodies and state officers ), the disputes are  not necessarily to be brought to the court  ( litigation )